Formulating Interreligious and Intercultural Ethnic Relations in Schools - Habibah Artini Ramlie; Habsah Omar; Mohd Syariefudin Abdullah; Norshahrul Marzuki Mohd Nor; Abdul Hair Beddu Asis (Human Resource Management Academic Research Society (HRMARS), 2023)
This study extends several preliminary studies conducted by the researcher regarding the aspects of interreligious and intercultural ethnic relations among students in selected schools and locations in the state of Sabah. This qualitative research involves library research and interview methods with six respondents from various fields, using a set of interview instruments. The objective of the study is to identify the scenario of interreligious and intercultural ethnic relations in schools as well as formulate a model appropriated from previous research. The research findings are then aligned with the findings of previous research as an overall summary of the relationships among students of various religions and cultures in schools. The final findings of the research propose an interreligious and intercultural model of ethnic relations among students that indirectly illustrate the harmony of diverse ethnicities, religions, and cultures in Sabah.